Analisis Faktor Ergonomi dengan Kelelahan Kerja dan Keluhan Musculoskeletal Disorders pada Pekerja Tenun Ikat di Desa Numponi Kabupaten Malaka - Yohana Ludowika Afean Pah; Luh Putu Ruliati; Mustakim Sahdan (Vitamin : Jurnal ilmu Kesehatan Umum, 2025)
Work fatigue and Musculoskeletal Disorders (MSDs) are common health issues among workers in the weaving industry. Fatigue often results from excessive workload, while MSD complaints typically include pain in the back, neck, wrists, elbows, and legs. This study used a cross-sectional design with a total sample of 45 active weavers in Numponi Village. The results showed significant associations between work fatigue and age (p=0.003), work duration (p=0.007), working posture (p=0.002), workload (p=0.014), and working hours (p=0.017), but not with temperature (p=0.561). Similarly, MSD complaints were significantly associated with age (p=0.001), work duration (p=0.003), working posture (p=0.025), workload (p=0.003), and working hours (p=0.002), with no significant link to temperature (p=0.826). It is recommended that weavers apply proper ergonomic principles to reduce the risk of fatigue and MSDs.